2019
DOI: 10.1155/2019/8201079
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate (DCA) and Cancer: An Overview towards Clinical Applications

Abstract: An extensive body of literature describes anticancer property of dichloroacetate (DCA), but its effective clinical administration in cancer therapy is still limited to clinical trials. The occurrence of side effects such as neurotoxicity as well as the suspicion of DCA carcinogenicity still restricts the clinical use of DCA. However, in the last years, the number of reports supporting DCA employment against cancer increased also because of the great interest in targeting metabolism of tumour cells. Dissecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(154 citation statements)
references
References 114 publications
(132 reference statements)
3
148
0
3
Order By: Relevance
“…Zhou et al [ 318 ], showed that combining of chemotherapy, together with inhibition of glycolysis by 3-bromopyruvate, effectively eradicates GCSCs in their hypoxic niches, where they exhibit resistant to mono-therapy by chemotherapeutic agents, and tend to reside in hypoxia and perform glycolysis for ATP generation in order to maintain their stemness and highly tumor forming capacity. In addition, in several cancer models, inhibition of PDKII by dichloroacetate has been demonstrated to reverse the metabolic shift from glycolysis to OXPHOS, increase ROS and promote apoptosis in CSCs and tumor cells [ 319 , 320 ].…”
Section: Treatments Of Cancer Emphasize Microenvironment Hypoxia In Cmentioning
confidence: 99%
“…Zhou et al [ 318 ], showed that combining of chemotherapy, together with inhibition of glycolysis by 3-bromopyruvate, effectively eradicates GCSCs in their hypoxic niches, where they exhibit resistant to mono-therapy by chemotherapeutic agents, and tend to reside in hypoxia and perform glycolysis for ATP generation in order to maintain their stemness and highly tumor forming capacity. In addition, in several cancer models, inhibition of PDKII by dichloroacetate has been demonstrated to reverse the metabolic shift from glycolysis to OXPHOS, increase ROS and promote apoptosis in CSCs and tumor cells [ 319 , 320 ].…”
Section: Treatments Of Cancer Emphasize Microenvironment Hypoxia In Cmentioning
confidence: 99%
“…The classic inhibitor of PDK1 is sodium dichloroacetate (DCA); however, its clinical trials has been terminated due to its severe side-effects ( 38 - 40 ). However, when used in co-treatment with the chemotherapeutic drug, paclitaxel (PTX), DCA markedly decreased cell autophagy, enhanced apoptosis and inhibited the proliferation of A549 and H1975 cells ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bioenergetic difference between cancer and normal cells may offer selective therapeutic targets, as dependence on glycolysis and lactic fermentation is only found in skeletal muscle cells during strenuous exercise. Side effects from continuous use of DCA has been few, but include reversible peripheral neuropathy [70]. However this effect seems to be limited to patients with mitochondrial diseases [93].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory phosphorylation of PDH by the PDKs leads to increased ux of pyruvate to lactate at the expense of mitochondrial pyruvate oxidation [67,68]. [69,70]. Dichloroacetate (DCA) is a natural occurring pyruvate analog, which acts as a PDK inhibitor, inducing increased mitochondrial pyruvate oxidation [69,70].…”
Section: The Capability Of Malignant Cells To Deregulate Cellular Enementioning
confidence: 99%
See 1 more Smart Citation